2023
DOI: 10.1007/s00192-023-05489-2
|View full text |Cite
|
Sign up to set email alerts
|

Supervised versus unsupervised pelvic floor muscle training in the treatment of women with urinary incontinence — a systematic review and meta-analysis

Abstract: Introduction and hypothesis This study synthesized the effects of supervised and unsupervised pelvic floor muscle training (PFMT) programs on outcomes relevant to women’s urinary incontinence (UI). Methods Five databases were searched from inception to December 2021, and the search was updated until June 28, 2022. Randomized and non-randomized control trials (RCTs and NRCTs) comparing supervised and unsupervised PFMT in women with UI and reported urinary symptoms, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There is high-level evidence to support the use of PFM training to improve the symptoms of incontinence (Hagen et al 2020;Kharaji et al 2023). A recent systematic review has also found that PFM training is beneficial in the treatment of individuals who experience incontinence during high-impact sports (Fukuda et al 2023).…”
Section: Establish a Baseline Awareness Of The Pelvic Floormentioning
confidence: 99%
“…There is high-level evidence to support the use of PFM training to improve the symptoms of incontinence (Hagen et al 2020;Kharaji et al 2023). A recent systematic review has also found that PFM training is beneficial in the treatment of individuals who experience incontinence during high-impact sports (Fukuda et al 2023).…”
Section: Establish a Baseline Awareness Of The Pelvic Floormentioning
confidence: 99%